Peculiarities of rotavirus infection in children with different genotypes of the lactase gene - Abaturov A.E.; Stepanova Y.Y.; Gerasymenko O.N. (Medičnì Perspektivi)
The aim was to study the peculiarities of rotavirus infection in children with various genotypes of the lactase gene LCT. Molecular genetic studies of LCT13910 gene polymorphism by polymerase chain reaction with electrophoretic detection were determined in the Institute of Genetic and Immunological basis of pathology and pharmacogenetics of "Ukrainian Medical Stomatological Academy", Poltava. According to the results of molecular genetic studies, all children were divided into three groups: the first group included 45 children with genotype C/C-13910, the second - 22 children with genotype C/T-13910, the third - 3 chil¬d¬ren with genotype T/T-13910. It is proved that in infants with rotavirus, the most common (63%) is genotype C/C-13910 of LCT gene. It is shown that a less severe form of the disease, which in most cases occurs without fever, a less duration of vomiting syndrome, a high incidence of respiratory syndrome, a less duration of illness are the peculiarities of rotavirus infection in children with genotype C/C-13910 LCT gene. Tendency to severe course with febrile fever, severe diarrhea, a high frequency of occurrence of expressed ketone blood syndrome, longer duration of disease may be considered to be features of rotavirus infection course in children with genotype C/T-13910 LCT gene.